1996
DOI: 10.1097/00006534-199604001-00001
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Relationship Between Strabismus and Head Posture in Patients with Frontal Plagiocephaly

Abstract: A prospective study was performed on 16 unoperated patients with frontal plagiocephaly to characterize the relationship between strabismus and abnormal head posture. Serial eye examinations were performed preoperatively and for 24 to 46 months following fronto-orbital advancement. In 14 patients (88 percent), preoperative clinical examination and CT scan indicated coronal plagiocephaly (synostotic); unicoronal synostosis was documented during fronto-orbital advancement in all these patients. Ten patients had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 13 publications
1
38
1
1
Order By: Relevance
“…Included among these are V-pattern strabismus, excyclotorsion, aniso-astigmatism, and amblyopia. The estimated incidence of V-pattern strabismus has been reported as 81%, 28 50%, 7 and 57.6% 21 in different studies. In a recent study comparing the ophthalmological findings of endoscopic strip craniectomy versus frontoorbital advancement, MacKinnon et al 22 found that the endoscopic craniectomy patients developed less severe V-pattern strabismus, excyclotorsion of the fundus, and range of aniso-astigmatisms.…”
Section: Discussionmentioning
confidence: 99%
“…Included among these are V-pattern strabismus, excyclotorsion, aniso-astigmatism, and amblyopia. The estimated incidence of V-pattern strabismus has been reported as 81%, 28 50%, 7 and 57.6% 21 in different studies. In a recent study comparing the ophthalmological findings of endoscopic strip craniectomy versus frontoorbital advancement, MacKinnon et al 22 found that the endoscopic craniectomy patients developed less severe V-pattern strabismus, excyclotorsion of the fundus, and range of aniso-astigmatisms.…”
Section: Discussionmentioning
confidence: 99%
“…The associated strabismus and ocular torticollis have been attributed to these orbital changes. [1][2][3][4][5][6][7][8] The majority of patients also develop aniso-astigmatism and, accordingly, may have an increased risk of amblyopia. 4,9 Although correction of unilateral coronal synostosis by fronto-orbital advancement (FOA) improves the orbital symmetry anterior to the axis of the globe, some posterior asymmetry may persist.…”
mentioning
confidence: 99%
“…Strabismus in this condition is common, frequently associated with apparent oblique muscle dysfunction ipsilateral to the side of the synostosis. 4,5,8,[11][12][13] Asymmetry of refractive error in unicoronal craniosynostosis is less well described in the literature. The authors of one study 5 reported an anisoastigmatism of 1.5 D or greater absolute cylindrical refractive error in 9 of 39 children with unicoronal craniosynostosis, involving the ipsilateral or the contralateral eye with almost equal frequency.…”
mentioning
confidence: 99%